Применение вычислительной аэродинамики к оптимизации лопаток турбомашин - Бойко, Анатолий Владимирович; Говорущенко, Юрий Николаевич; Бурлака, Максим Васильевич (НТУ "ХПИ", 2012)
Рассматриваются проблемы применения вычислительной аэродинамики к оптимизации лопаток турбомашин на примере создания алгоритма оптимизации сложного тангенциального навала решеток осевых турбин. Исследовано влияние простого и сложного тангенциального навала на структуру трехмерного течения, коэффициент интегральных потерь и расход рабочего тела в кольцевых направляющих решетках осевых турбин. Предназначена для научных сотрудников, специалистов в области энергомашиностроения, а также аспирантов и студентов соответствующих специальностей.

The publication considers the problems of the application of aerodynamics computing to the optimization of turbomachine blades using the example of the complex tangential lean optimization of axial turbine blades with reduced optimization time and precise observance of the mass flow rate. A review of current research on spatial flow in turbine cascades and the reduction of secondary flow losses is carried out. Aspects of turbine blade geometry formation and the creation of grids in turbine blade passages, and their storage are considered in detail. The influence of simple and complex tangential lean on a threedimensional flow structure, the factor of integrated losses and the mass flow rate in the guide blade rim of axial turbines is investigated. The algorithm developed using two parametrical blade models is tested at different relations of blade rim throat to height while preserving the mass flow rate through it. The resulting analysis examines the reasons for the increased aerodynamic efficiency of the blade rim of axial turbines as explained by the physics of aerodynamic phenomena. The publication is intended for research associates, experts, graduate students and students in the field of power mechanical engineering.
Application of computational fluid dinamics to optimization of turbomachine blades
Keywords: решетки осевых турбин; турбомашины; аэродинамическая эффективность; лопатки турбин; файлы хранения лопатки; формат STL; формат OFF; формат CURVE; формат RTZT; формат CUR; стекинг; трехмерная расчетная сетка; CFD инструментарий; турбулентность